Looking beyond the bridge: How temporary agency employment affects labor market outcomes - Elke J. Jahn; Michael Rosholm (Institute for the Study of Labor (IZA), 2010)
We perform a comprehensive analysis of the stepping-stone effect of temporary agency employment on unemployed workers. Using the timing-of-events approach, we not only investigate whether agency employment is a bridge into regular employment but also analyze its effect on post-unemployment wages and job stability for unemployed Danish workers. We find evidence of large positive treatment effects, particularly for immigrants. There is also some indication that higher treatment intensity increases the likelihood of leaving unemployment for regular jobs. Our results show that agency employment is even more effective in tight labor markets, where firms use agency employment primarily to screen potential candidates for permanent posts. Finally, our results suggest that agency employment may improve subsequent match quality in terms of wages and job duration.
Keywords: C41; J64; J30; J40; 330; Temporary agency employment; stepping stone; employment stability; wages; Arbeitsmarktpolitik; Leiharbeit; Wirkungsanalyse; Berufliche Integration; Lohn; Arbeitsplatzsicherung; Migranten; Schätzung; Dänemark